Two formative communities in the middle valley of Lurín: a comparison of the sites of Anchucaya and Chillaco - Milan, Christopher (2021)
Anchucaya and Chillaco are two villages from the Initial Period (1800 - 800 BC) that occupied the middle valley of Lurín, on the central coast of Peru. Although there are several similarities between the two sites, the differences indicate that the villages had two distinct populations. It reveals how the developments of this era have affected rural settlements and the ways in which communities can express their autonomy.